From Offline toward Real Time: A Hybrid Systems Model Checking and CPS Codesign Approach for Medical Device Plug-and-Play Collaborations - Li, Tao; Tan, Feng; Wang, Qixin; Bu, Lei; Cao, Jian-Nong; Liu, Xue (IEEE transactions on parallel and distributed systems, 2014)
Hybrid systems model checking is a great success in guaranteeing the safety of computerized control cyber-physical systems (CPS). However, when applying hybrid systems model checking to Medical Device Plug-and-Play (MDPnP) CPS, we encounter two challenges due to the complexity of human body: 1) there are no good offline differential equation-based models for many human body parameters; 2) the complexity of human body can result in many variables, complicating the system model. In an attempt to address the challenges, we propose to alter the traditional approach of offline hybrid systems model checking of time-unbounded (i.e., infinite horizon, a.k.a., long run) future behavior to online hybrid systems model checking of time-bounded (i.e., finite horizon, a.k.a., short run) future behavior. According to this proposal, online model checking runs as a real-time task to prevent faults. To meet the real-time requirements, certain design patterns must be followed, which brings up the codesign issue. We propose two sets of system codesign patterns for hard real time and soft real time, respectively. To evaluate our proposals, a case study on laser tracheotomy MDPnP is carried out. The study shows the necessity of online model checking. Furthermore, test results based on real-world human subject trace show the feasibility and effectiveness of our proposed codesign.